The design and evaluation of an ozone contactor-reactor for color and organic matter removal in distellery wastewater - Mercader, Shalom Brian R. (2010)
The study focused on the development of ozone contactor-reactor design for the purpose of eleiminating melanoidin, which is a major by-product of distillation industries and identified as the major colorant in sugarcane molasses wastewater.